Penyuluhan Untuk Peningkatan Kemampuan Wirausahaan Digital Siswa SMK - Yusuf Suhardi; Arya Darmawan; Zulkarnaini Zulkarnaini; Erizal Azhar; Meita Pragiwani (Bagian Pengelolaan Jurnal dan Penerbitan - Sekolah Tinggi Ilmu Ekonomi Indonesia Jakarta (BPJP - STEI), 2022)
This counseling is intended for vocational school students because its education focuses on skills for vocational graduates whose graduates are not meant to go to college but to work and have an independent business. In general, there are also many vocational schools for underprivileged families, so that after graduation, it is more about how to get a job as soon as possible. But on the other hand, the work is also not easy because of high competition and high company demands or requirements. The material provided includes the following digital era entrepreneurship, online business entrepreneurship, building a superior generation with an entrepreneurial spirit, and how to start a business with e-marketing. Delivered with lecture and question and answer methods accompanied by interesting videos make it easier for participants to understand clearly.